Adaptive Pedagogical Innovation Based on the Flipped Classroom as an Effective Strategy for Educational Transformation in Higher Education - Amanah, Nihayatul; Mardotillah, Wildan Nur (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This article discusses adaptive pedagogical innovations in the learning process in the form of flipped classrooms as an effective strategy for transforming higher education. The flexibility and personalization offered by this method allow students to learn according to their own styles and paces. This study employs qualitative research using a literature review method from scientific sources such as journals, books, and others, as well as interviews with several students from UIN KH Abdurrahman Wahid Pekalongan who are involved in the learning process of classes that have implemented the flipped classroom method. The study found that in higher education, the flipped classroom approach can optimize the use of technology in the classroom and promote the development of critical thinking skills, independence, and student responsibility. However, the implementation of this model still faces several challenges, including the readiness of digital infrastructure, the technological skills of faculty and students, the development of relevant and engaging learning content, and enhancing students' understanding of the use of artificial intelligence (AI) to prevent excessive reliance on such technology. With support from the university, enhanced faculty capabilities and skills, and appropriate use of technology, the flipped classroom learning model can serve as a key driver for transforming higher education toward a more adaptive, inclusive, and 21st-century needs-based approach.